Detection of Proteus mirabilis as foodborne disease bacteria in carcass of broiler chickens (Gallus domesticus) (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2018)
Poor hygiene of traditional market often resulted in bacterial contamination of chicken meat including Proteus mirabilis which is also serve as a foodborne disease in human. Proteus mirabilis is pathogenic to humans because it can produces the urease which results in urinary tract infections (UTI). This research aimed to determine the presence of Proteus mirabilis bacteria in chicken meat sold in some traditional markets in the city of Makassar. The samples used in this study (24 samples) were obtained from 6 Traditional Markets in Makassar. Colony observation, Gram staining and biochemical test were used to identify Proteus mirabilis in the chicken carcass. Positive samples were confirmed by Polymerase Chain Reaction (PCR). The result of this study revealed that 12.5% (3/24) were positively contaminated with Proteus mirabilis. The conclusion of this study was that chicken meat sold in the traditional market of Makassar has already been contaminated with Proteus mirabilis
Keywords: Proteus mirabilis; foodborne disease; urinary tract infection; carcass chicken; traditional market